Behavior Sequencing Violent Episodes in Forensic Youth Populations. (January 2022) - Keatley, David A.; Starritt, James; Parke, Adrian; Joyce, Tara; Clarke, David D.
Every year, more children and youths are sent to Secure Children's Homes while moving through the criminal justice system. Aggressive and violent incidents in these settings are common, and staff are often required to intervene and restrain violent individuals. The research literature has many examples of aggression and violence questionnaires and measures; however, for staff in communal areas it is the observable behaviors that they react to most. The current research, therefore, analyzed observable behaviors leading-up to violent episodes, and used Behavior Sequence Analysis to highlight the typical chains of behaviors that tend toward violence. The outcomes of this research show pathways to violence that staff can use to highlight potential spirals of aggression and violence. The current results show the links between non-confrontational behaviors (e.g., talking) through to more confrontational (staring, approaching, and pushing others). Overall, the research forms the foundation for future investigation into these and similar settings and outlines a novel approach to understanding violence escalation in a way that can be interpreted and used by service staff.